CREDIT RESTRUCTURING AND FINANCIAL PERFORMANCE BEFORE AND DURING THE COVID-19 PANDEMIC - Irwan, Irvan Fadhela; Reynaldi, Vabian; Paulina, Wella; wahyuni, Nurul Sri; Aghniya, Syanis Syifa; Hadi, Dudi abdul (CENTRAL ASIA AND THE CAUCASUS, 2022)
Low financial performance occurred because bad credit during the Covid 19 pandemic continued to rise. The study aimed to find out if financial performance fell due to credit restructuring at the time of the Covi 19 pandemic. This study was conducted descriptively and wilcoxon test in the form of population is banking industry and the sample is 10 banks in Indonesia based on data in accordance with the bank's industrial financial statements. Based on the results of research that can be credit restructurization affects current financial performance in Indonesia. The results showed that from 20 samples of data obtained from financial statements comparing NPL and return on assets were significantly affected but showed that the average banking company still has the ability to meet its obligations at the time of this pandemic, despite extended credit restructuring. Although the financial performance of banking companies is quite decreased.